Ethanolic extract of Ocimum Gratissimum (Scent Leaf) leaves improves haematological parameters in restrain-stressed rats - K.K. Anachuna; E.G. Moke; J.C. Oyem; A.I. Omogbiya; T.M.E. Daubry; E.I. Ebuwa (Journal of Applied Sciences and Environmental Management, 2021)
Stress alters system physiology as well as humoral immunity and hematology, and its problems have become a global issue. The present study was designed to investigate effects of the use of traditional herbs such as Ocimum gratissimum (OG) on hematological parameters in stressed rats. We subjected adult female Wistar rats to prolonged restrained stress for 14 days and administered 100 mg/kg, 200 mg/kg, 400 mg/kg of OG leaf extract and Vitamin C respectively for 14 days. Animals (200-250 g) were sacrificed by cervical dislocation at day 0, day 7 and Day 14 so as to assess the dose and time dependent effect of the extract. Findings revealed that OG leaf extract caused a dose-dependent significant protective effect (P<0.05) on the packed cell volume (PCV), total white blood cell (WBC) count, haemoglobin (Hb), platelet count and total red blood cell (RBC) count compared to Vitamin C treated group. Our study confirms that OG leaf extract is better at improving haematological parameters of restrain stressed rats compared to Vitamin C and it was more effective in animals that were administered 100 mg/kg and 400 mg/kg of the extract. The result indicates that OG leaf extract could alleviate prolonged exposure to stress by lowering PCV, total WBC, total RBC, hemoglobin count and elevating blood platelets.